2017
DOI: 10.1037/pap0000132
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in the dissertation writing process: Barrier, block, and impasse.

Abstract: In this paper, I explore the kinds of difficulties arising during the writing process as seen in students embarking on, engaged in the midst of, and at the stage of completion of a dissertation. I am specifically concerned with the dissertation completed as a part of a humanities-based program in contrast to an empirical piece of work based in a scientifically oriented program. Contained in this process can be the experience of a terror of what the dissertation represents, a breakdown in the relationship to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Then, we can replace the truncation length T with period o T and use Fourier series to find the spectrum of the signal. (18) and by the Baseval's theorem for periodic functions:…”
Section: Principle Of Mallat Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we can replace the truncation length T with period o T and use Fourier series to find the spectrum of the signal. (18) and by the Baseval's theorem for periodic functions:…”
Section: Principle Of Mallat Algorithmmentioning
confidence: 99%
“…The literature [17] explored the impact of children's anxiety situations on expressive writing at the level of developmental and gender differences, and the study showed that expressive writing could alleviate anxiety situations and is important for children's healthy development. The literature [18] explored the difficulties that arise during the writing process and the various psychological states, including defensive anxiety as well as inhibitory factors such as avoidance anxiety, emphasizing that these psychological states are not singular but intersecting and that the psychological states change with the environment. This paper first investigates the principle of the EEG-based emotion recognition model, preprocesses the collected EEG signals, extracts and analyzes the time domain characteristics, frequency domain characteristics and time-frequency domain characteristics of EEG signals, and then performs emotion recognition on the selected features of EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…The network structure with the maximum posterior probability at this time is the network structure that makes maximum. Therefore, the Bayesian scoring function of this network structure, i.e., the number of MAP measures, can be defined as (11) Assume that the prior probabilities obey: (12) i.e., the Dirichlet distribution described by this equation, then we have (13) (14) Among them are:…”
Section: Network Structure Learning Based On Scoring Searchmentioning
confidence: 99%
“…The undergraduate thesis is the most important teaching practice that takes up the longest number of hours in the whole teaching process and can best measure the comprehensive level of students. It occupies an important position in undergraduate teaching work and is also an important aspect of measuring and testing the teaching quality of higher education institutions [6][7]. Therefore, in the evaluation of the level of undergraduate teaching work carried out by the Ministry of Education, the thesis is listed as an important secondary indicator among the primary indicators of teaching effectiveness in the evaluation index system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation